TRADISI UPACARA KEMATIAN SUKU BATAK TOBA DESA NAGASARIBU KECAMATAN LINTONGNIHUTA KABUPATEN HUMBANG HASUNDUTAN SUMATERA UTARA - Damanik, Asrida Damanik; Melay, Ridwan Melay; ', Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :The tradition there is a tradition in the village Nagasaribu Toba Batak tribe funeral ceremony where traditional ceremonies of death are classified according to age and status of the person who died. The traditional ceremony increasingly laden death if untreated indigenous people dead: Has married but without children, had been married to abandon their children are still young, have children who are grown up, there's even married but does not have grandchildren , she already had grandchildren, but there are still children who are unmarried and have had grandchildren but not necessarily all of the children.Researchers used qualitative research methods to study descriptive data. In the data collection researchers used interview, observation and documentation. Data analysis was conducted by the authors is to collect data and then analyze the data. The result of this study are ceremonial death Batak Toba, for those who die for the people who have been married have not had children, has been married to leave small children and have had children who have grown up, there’s even married, but do not have a custom grandchildren used very simple, namely prayer. For who already have grandchildren, but there are still children who are not married and have used custom may use tor-tor and drumbs but can not be called great because there is his custom unmarried and to that already have grandchildren but not necessarily all of the children, indigenous customary use is already using tor-tor and drums. Keywords: Tradition, Ceremony, Death.